Melanie King: Tea, Coffee & Chocolate. How we fell in love with caffeine - Jaine, Tom (Petits Propos Culinaires, 2015)
Melanie King: Tea, Coffee & Chocolate. How we fell in love with caffeine: Bodleian Library, 2015: 170 pp., hardback, £9.99.